Tax Revenues in the Context of Economic Determinants - Alena Andrejovská; Veronika Puliková (Montenegrin Journal of Economics)
Despite the general recognition that taxes are generally a strong policy tool for assessing the macroeconomic impact of the country's alternative tax policies, taxes are often weakened by restrictions on tax revenue measurement. The aim of the contribution is to quantify the impact of selected macroeconomic indicators (gross domestic product, level of employment, public debt, foreign direct investments, effective tax rate, statutory tax rate) on the total amount of tax revenues, taking into account the tax competitiveness of the 28 EU member states. There was used methods of three models of regression analysis: the pooling model, the fixed effects model and the random effects model. The hypothesis that the gross domestic product has the greatest impact on tax revenue has been tested. In conclusion, the analysis confirmed that the strongest correlation is between tax revenues and employment rate. Followed by foreign direct investment and gross domestic product. Increasing these determinants by 1 mil. € (increase in employment by 1%) would increase tax revenues by 10 072 mil. € at the employment rate, by 383.1 thousand € for gross domestic product and by 434.2 thousand € for foreign direct investment.